A Cooperative Pedagogical Program Linking Preschool and Foundation Teachers: A Pilot Study. Issue 3 (September 2016) - Dunham, Annette; Skouteris, Helen; Nolan, Andrea; Edwards, Susan; Small, Jennifer
THE TRANSITION TO FORMAL schooling is a significant milestone for young children and their families. Congruence between an early childhood setting and school experience is known to impact on children's positive start to school. Despite policy efforts at the Victorian state level, preschool educators and Foundation teachers do not have a strong understanding of the curriculum, pedagogical and assessment practices used in the alternate setting. This paper reports on the 'Alliance Project' that sought to support preschool educators and Foundation teachers to work cooperatively to better understand each other's practices. Drawing from sociocultural theory, the Alliance Project employed an interventionist methodology to work with preschool educator and Foundation teacher pairings on a joint planning initiative. Participants on the Alliance Project gained increased familiarity with the alternate setting's curriculum, pedagogy and assessment practices, and an increased capacity to work cooperatively across both settings to address the needs of transitioning children.